Relationship between Adversity Quotient and Students' Mathematics Learning Outcomes for Distance Learning in Junior High Schools - Laili, Nurul (Journal of Humanities and Social Sciences (JHASS), 2021)
Masa pandemi ini sangat mempengaruhi perkembangan siswa dalam melaksanakan kegiatan pembelajaran sehingga harus melakukan pembelajaran jarak jauh. Siswa dikatakan berhasil mengikuti pembelajaran dengan baik dengan melihat hasil belajarnya. Adversity Quotient merupakan salah satu kecerdasan yang dimiliki untuk mengenali kesulitan diri sendiri dan mampu mengubahnya sebagai potensi untuk mengatasi kesulitan. Hal ini penting dilakukan mahasiswa dalam kegiatan pembelajaran jarak jauh kali ini. Penelitian ini bertujuan untuk mengetahui hubungan antara Adversity Quotient dengan hasil belajar matematika. Subjek dalam penelitian ini adalah siswa kelas VII di Depok. Metode penelitian yang digunakan adalah survei dengan analisis data deskriptif. Pengumpulan data menggunakan media Google Form dengan menyebarkan kuesioner yang berjumlah 16 item pernyataan. Responden dalam penelitian ini berjumlah 130 siswa, dengan 61 siswa laki-laki dan 69 siswa perempuan. Hasil yang diperoleh dalam uji korelasi penelitian ini memiliki nilai sig. 0,000 <0,05. Dapat disimpulkan bahwa terdapat hubungan yang signifikan dan positif antara Adversity Quotient dengan hasil belajar siswa. Relationship between Adversity Quotient and Students' Mathematics Learning Outcomes for Distance Learning in Junior High Schools Abstract: This pandemic period greatly affects the development of students in carrying out learning activities so they have to do distance learning. Students are said to be successful in following the learning well by seeing the learning outcomes. Adversity Quotient is one of the intelligences possessed to recognize one's own difficulties and be able to change them as potential to overcome difficulties. This is important for students in distance learning activities at this time. This study aims to determine the relationship between Adversity Quotient and mathematics learning outcomes. The subjects in this study were 7th grade students in Depok. The research method used was a survey with descriptive data analysis. Collecting data using Google Form media by distributing questionnaires with a total of 16 statement items. Respondents in this study were 130 students, with 61 male students and 69 female students. The results obtained in the correlation test of this study have a sig value. 0.000 <0.05. It can be concluded that there is a significant and positive relationship between Adversity Quotient and student learning outcomes. Keywords: Adversity Quotient, Distance Learning, Mathematics Learning Outcomes.